Racing Strategy in Rowing During the Sydney Olympic Games - Kleshnev, V. (coachesinfo.com)
It is common opinion that an even distribution of boat speed during the race is the most beneficial from a hydrodynamic point of view. This appears to be true, as telemetry measurement has proved a strong correlation between boat speed variation and its efficiency, i.e. amount of speed lost because of variation. On average, each percent of variation decreases boat speed by 0.25%, i.e. 0.75 sec over 2000 m. Therefore, an average 2% of boat speed variation during the race causes a loss of 1.5 sec at finish. This amount of time may appear non significant, however it could prove the difference between a bronze and a gold medal. Should rowers follow this even pattern of the race strategy? No, they should not do it. Because, two other factors exist, which have more influence than the previous one. The first is a physiological factor. Energy production in rowing is 70-80% from aerobic sources . A rapid rise in oxygen consumption requires significant anaerobic workload at the start of the race. The anaerobic source is more powerful, therefore the first piece of the race should be faster than others. However, it should not be too fast, otherwise rowers must tolerate very high oxygen debt and lactate concentration during the race. The second is a psychological factor. Rowers can more easily control the race and obtain some psychological advantage when they lead the race from the start. The analysis of the race strategy at the Sydney Olympics have confirmed the above proposals. The total race pattern during the finals was: +2.8%, -1.2%, -1.3%, -0.1% (speed at each 500m piece relative to average speed during 2000m race). It was found that race strategy significantly depended on race type (slower finish in heats) and boat type (more even in bigger boats). Some differences were found between race strategies of rowers from different countries. Medal winners had 0.6% slower first 500m and the same amount faster final 500m than other competitors. A new classification of race strategies was established, which consisted of 12 patterns. It was found that the most medal winners used patterns with a faster race finish.